Antibody-Dependent Cellular Cytotoxicity Responses to Seasonal Influenza Vaccination in Older Adults. (2nd November 2017) - Vanderven, Hillary A; Jegaskanda, Sinthujan; Wines, Bruce D; Hogarth, P Mark; Carmuglia, Sarina; Rockman, Steven; Chung, Amy W; Kent, Stephen J
Abstract : In older adults, the antibody-dependent cellular cytotoxicity (ADCC) response to seasonal trivalent influenza vaccination mirrored the hemagglutination inhibiting (HAI) antibody response. Pre-existing ADCC antibodies against circulating strains of influenza were common among older adults, even when HAI titers were low. Abstract: Background: Older adults are at high risk of influenza disease, but generally respond poorly to vaccination. Antibody-dependent cellular cytotoxicity (ADCC) may be an important component of protection against influenza infection. An improved understanding of the ADCC response to influenza vaccination in older adults is required. Methods: We studied sera samples from 3 groups of subjects aged ≥65 years (n = 16–17/group) receiving the 2008/2009 seasonal trivalent influenza vaccine (TIV). Subjects had minimal pre-existing hemagglutination inhibiting (HAI) antibodies and TIV induced either no, low, or high HAI responses. Serum ADCC activity was analyzed using Fc receptor cross-linking, NK cell activation, and influenza-infected cell killing. Results: Most subjects from TIV nonresponder, low responder, and high responder groups had detectable ADCC antibodies prevaccination, but baseline ADCC was not predictive of HAI vaccine responsiveness. Interestingly, ADCC and HAI responses tracked closely across all groups, against all 3 TIV hemagglutinins, and in all ADCC assays tested. Conclusions: Older adults commonly have pre-existing ADCC antibodies in the absence of high HAI titers to circulating influenza strains. In older vaccinees, ADCC response mirrored HAI antibodies and was readily detectable despite high postvaccination HAI titers. Alternate measures of vaccine responsiveness and improved vaccinations in this at-risk group are needed.